2004
DOI: 10.1163/1568539042948088
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Diminishes Courtship Behaviour and Stimulates Fanning in Nesting Male Three-Spined Sticklebacks, Gasterosteus Aculeatus

Abstract: The male stickleback displays a gradual change in reproductive behaviour as the eggs develop over the nesting cycle, with a decrease and cessation of courtship behaviour (e.g. zigzag dance) and an increase in fanning, i.e. ventilation of the nest and eggs. Prolactin (PRL) is known to stimulate fanning behaviour in several teleosts, including the stickleback, in which furthermore the PRL cells of the pituitary have been found to be more active during the later parental phase than during the initial sexual phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…For example, prolactin (PRL) has been implicated in the control of parental care in vertebrates, including fishes (Slijkhuis et al, 1984). A functional role for PRL in the control of fanning behaviour in sticklebacks was confirmed by Pall et al (2004), who demonstrated that PRL administration increased fanning behaviour in nesting males. Bell (2001) determined that gonadal steroids have contrasting effects on conspecific-oriented and nest-oriented behaviours during stickleback courtship.…”
Section: Reproductive Behaviourmentioning
confidence: 99%
“…For example, prolactin (PRL) has been implicated in the control of parental care in vertebrates, including fishes (Slijkhuis et al, 1984). A functional role for PRL in the control of fanning behaviour in sticklebacks was confirmed by Pall et al (2004), who demonstrated that PRL administration increased fanning behaviour in nesting males. Bell (2001) determined that gonadal steroids have contrasting effects on conspecific-oriented and nest-oriented behaviours during stickleback courtship.…”
Section: Reproductive Behaviourmentioning
confidence: 99%
“…In particular, PRL was found to be of major importance for the regulation of brood care (Blüm and Fiedler, '65;Slijkhuis et al, '84;Tacon et al, 2000;Páll et al, 2004). In species that do not show natural brood care behavior, the application of PRL alone does not elicit such behavior (Blüm,'74), but in species showing brood care it could be elicited or intensified by PRL.…”
mentioning
confidence: 99%
“…Nest fanning behaviour provides a flow of oxygenated water to ventilate developing eggs in the nest, and parental fanning activity has been shown to be under PRL control in several species [80]. An early experiment showed increased fanning behaviour in male and female angelfish (Pterophyllum scalare) and brown discus (Symphysodon haraldi) following PRL injection, even in the absence of eggs [11,12].…”
Section: Fanningmentioning
confidence: 99%
“…This increased activity was found to be dose-dependent, and higher doses of PRL inhibited fanning behaviour. PRL also induces fanning in other species of fish, including wrasse males (Symphodus ocellatus) [reviewed in 12] and stickleback males [80]. Experimental treatment of convict cichlid (Amatitlania nigrofasciata) females and male bluegills (Lepomis macrochirus) with PRL inhibitors results in decreased fanning behaviour [reviewed in 43,55].…”
Section: Fanningmentioning
confidence: 99%